2023
DOI: 10.3390/ijms241914740
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Hypofunction of the Masseter Leads to Molecular and 3D Morphometric Signs of Atrophy in Ipsilateral Agonist Masticatory Muscles in Adult Mice

Julián Balanta-Melo,
Andrea Eyquem-Reyes,
Noelia Blanco
et al.

Abstract: Mice are commonly used to study mandibular dynamics due to their similarity in chewing cycle patterns with humans. Adult mice treated unilaterally with botulinum toxin type A (BoNTA) in the masseter exhibit atrophy of this muscle characterized by an increase in the gene expression of atrophy-related molecular markers, and a reduction in both muscle fiber diameter and muscle mass at 14d. However, the impact of this muscle imbalance on the non-treated masticatory muscles remains unexplored. Here, we hypothesize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Consequently, any alteration within masticatory system structures can reach implications for health across multiple domains, affecting, in addition, other components of the same system [18,20]. In addition, any disturbance in a masticatory muscle, such as a decrease in masseter muscle mechanical activity caused by the inherent paralytic effect of BoNT-A as an aesthetic treatment for MH, may alter the operation pattern of other masticatory muscles, leading to shifts in mandibular kinematics and masticatory coordination [21]. On the contrary, studies have shown that changes in muscular coordination with BoNT-A in chewing muscles can be advantageous in managing sialorrhoea (drooling) in patients with Parkinson's disease [22], as well as in reducing muscle hypertrophy and stiffness and enhancing the facial contours and aesthetics in people with MH [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, any alteration within masticatory system structures can reach implications for health across multiple domains, affecting, in addition, other components of the same system [18,20]. In addition, any disturbance in a masticatory muscle, such as a decrease in masseter muscle mechanical activity caused by the inherent paralytic effect of BoNT-A as an aesthetic treatment for MH, may alter the operation pattern of other masticatory muscles, leading to shifts in mandibular kinematics and masticatory coordination [21]. On the contrary, studies have shown that changes in muscular coordination with BoNT-A in chewing muscles can be advantageous in managing sialorrhoea (drooling) in patients with Parkinson's disease [22], as well as in reducing muscle hypertrophy and stiffness and enhancing the facial contours and aesthetics in people with MH [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…By diminishing masseter muscle contraction due to BoNT-A injections, a potential increase in temporalis volume and thickness could be expected, due to an increased compensatory contraction activity in temporalis muscle. In addition, an animal study has proved that the anterior temporalis exhibits an increase in thickness due to a compensatory mechanism for reduced function of the masseter muscles [21].…”
Section: Discussionmentioning
confidence: 99%